How are endemic and widely distributed bromeliads responding to warming temperatures? A case study in a Brazilian hotspot - Neves Chaves, Cleber Juliano [UNESP]; Santos Leal, Barbara Simoes [UNESP]; Lemos-Filho, Jose Pires de (Elsevier B.V., 2018)
The increase in mean global temperature is causing extensive changes in ecosystems. However, little is yet known about the heat tolerance of neotropical plant species. Here, we investigate heat tolerance variation in both restricted and widely distributed bromeliad species co-occurring in campo rupestre, a megadiverse ecosystem in central and eastern Brazil. We determined the heat tolerance of the photosynthetic apparatus using chlorophyll fluorescence measurements to test if the endemic species Vriesea minarum is more heat sensitive than two widely distributed species, Vriesea bituminosa and Aechmea nudicaulis. Furthermore, we tested if the distinct photosynthetic metabolisms of the species, sun exposure, and rainfall seasonality of campo rupestre influence this outcome. Our results show that, contrary to our expectations, the endemic campo rupestre species did not show the greatest heat sensitivity, but did have one of the lowest heat tolerance plasticities. The CAM bromeliad A. nudicaulis was more heat tolerant than the other bromeliad species, but both heat tolerance and its plasticity are highly affected by sun exposure and the rainfall seasonality of campo rupestre. The low values and plasticity of V. minarum thermal tolerance could indicate that the threat of global warming could be greater for this campo rupestre endemic species. Our results also indicate that heat tolerance, especially the ability to withstand stressful temperatures for a long time, is an important parameter that differentiates the ecological strategies of these bromeliads species. (c) 2017 Elsevier GmbH. All rights reserved.
Keywords: Thermal tolerance; Climate change; Bromeliaceae; Species range; CAM; C-3